Development of a digital controller with data acquisition to a test bench for eletric motors - Pedrosa, Delfim Duarte Rolo (2012)
The electric motors’ test benches are greatly used by electric motors manufacturers and drive system designers. In this paper it is described the conversion process of an older manually controlled test bench, in an automatic digitally controlled one with integrated data acquisition system. The renewed test bench is based in a two quadrant eddy current electromagnetic brake, in which the manual torque controller and analog indicator have been replaced by an automatic digital controller, by which is possible to predefine a torque profile for the test. With the data acquisition system it is possible the acquisition and recording of speed, torque and internal temperature on the brake. Special focus is given to the power converter used to control the current in the electromagnetic brake and to the torque data acquisition system, namely, the calibration of the load cell.